Micro and macro structural brain plastic changes induced by sexual experience in male rats - Zacnite Mier-Quesada; Lorena Gaytán-Tocaven; Alberto Prado; Raúl G. Paredes (PLoS ONE, 2025)
Sexual behavior induces brain plastic changes such as neurogenesis, but few studies have evaluated possible changes in synaptic plasticity produced by sexual experience. In the present study, we assessed whether two aspects of sexual behavior in male rats, sexual incentive motivation and sexual execution in a partner preference test, could induce micro and macrostructural changes in brain regions involved in controlling sexual behavior belonging to the socio-sexual behavior network and the mesolimbic reward circuit. The microstructural changes were evaluated by synaptophysin immunofluorescence expression. We assessed the macrostructural changes using manganese-enhanced magnetic resonance imaging and volume changes by magnetic resonance imaging. Our results indicate that the mesolimbic reward circuit underwent plastic changes at the level of synaptophysin expression, mainly in the partner preference test group. In the socio-sexual behavior network circuit, an increase in brain activation was observed primarily in the sexual incentive motivation group. When analyzing the activation of the whole brain, the statistical map showed a significant increase in weeks 5 and 10 compared to week 1 in the sexual incentive motivation group. The results confirm that different neuroplastic changes, including synaptophysin expression, brain activation, and volume changes, occur during the acquisition of sexual experience.